Life Experiences of Obesity Communities in Bulukumba District : Phenomenological Study - Muriyati; Hamdana (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Globally, obesity has entered the epidemic proportion, with at least 2.8 million people dying every year due to obesity, for Indonesia itself the incidence of obesity has also increased significantly in every region with Jakarta's first ranking of 11.4%. The purpose of this study was to describe the life experiences of people who are obese in Bulukumba Regency. The method in this study uses qualitative research (cases) and takes a sample of 6 respondents with obesity. The data in this study were collected through in-depth interviews on selected subjects and analyzed using thematic analysis. The analysis results obtained four themes, namely (1) Knowledge, (2) Diet, (3) physical activity (4) Paradigm. The conclusions and suggestions of this study are the level of knowledge, diet, physical activity and a person's perspective on obesity greatly influence the incidence of obesity. Researchers suggest that future researchers dig deeper into the causes of obesity.